Al-doped walnut-shell-like P2-type Na2/3Ni1/3Co(1/3-x)Mn1/3AlxO2 as advanced sodium ion battery cathode materials with enhanced rate and cycling performance. (20th July 2020) - Fu, Junrui; Huang, Haijian; Shi, Kun; Chen, Fei; Yang, Zeheng; Zhang, Weixin
Abstract: Sodium layered oxides are considered to be promising candidates as sodium ion battery cathode materials due to their layered structure which is beneficial for fast Na-ion diffusion. However, their practical application is hampered by the rapid capacity decay as a result of the multiple irreversible phase transitions and the volume expansion during operation. Herein, by regulating morphology through the surfactant of tween 80 and partially substituting Co 3+ with Al 3+ ions, we successfully prepared Al-doped P2-type Na2/3 Ni1/3 Co(1/3- x ) Mn1/3 Al x O2 with uniform walnut-like porous and hollow structure. As the result of the synergy of Al-doping and morphology design, the resulting material exhibits good accommodation of volume change and suppressed phase transitions during charge/discharge processes. Moreover, the optimization on the Al-doping content is carefully investigated and the results demonstrate that the Na2/3 Ni1/3 Co(1/3- x ) Mn1/3 Al x O2 with x  = 0.03 exhibits the best performance with a capacity of 74.7 mA h g −1 delivered at 10C and a capacity retention of 76.6% achieved after 150 cycles. Further study reveals that the performance of the P2-type Na2/3 Ni1/3 Co(1/3- x ) Mn1/3 Al x O2 is closely related to the limiting effect of the Al-doping on the phase transitions as well as the charge transfer resistance. Ex-situ scanning electron microscope and X-ray powder diffraction results uncover the morphological stability and the electrochemical reversibility of the Na2/3 Ni1/3 Co(1/3-x) Mn1/3 Alx O2 with x = 0.03. This work introduces the synergistic combination of doping and morphology design as an efficient method to enhance the Na-ion storage performance, which may provide a promising strategy for developing advanced sodium ion battery cathode materials.